(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
Gold mining companies have been known to use cyanide to extract gold from minerals. The indiscriminate use of cyanide presents a major issue in the environment. The used of linearisation methods using natural logarithm transformation is inaccurate, even though is standard and can just give an estimated value for the sole parameter measured; the specific growth rate. In this study, various cyanide concentrations ranging from 0 - 350 mg/L was used. Seven different mathematical models such as such as modified Logistics, modified Gompertz, modified Richards, modified Schnute, Baranyi-Roberts, Von Bertalanffy and most recent Huang were used to get values for the above constants or parameters from bacterial growth Pseudomonas putida on cyanide. The best model was found to be modified Logistics with the lowest AICc and RMSE value. The modified Logistics parameters such as Ymax (bacterial growth upper asymptote), Î» (lag time), Âµmax (maximum specific bacterial growth rate) and A or Y0 (bacterial growth lower asymptote) were found to be 2.41 (95% confidence interval of 2.37 - 2.45), -3.16 (95% confidence interval of -4.64 to -1.68) and 0.12 (95% confidence interval of 0.11 to 0.13). This is the first report of growth mathematical modelling of the effect of cyanide on Pseudomonas Putida (Naun-16).